In Memoriam: A Memoir for Our Fallen "Heroes". Issue 4 (13th July 2020) - Chaurasia, Bipin; Deora, Harsh; El-Ghandour, Nasser M F; Oyesiku, Nelson M; Chaurasia, Raushan Kumar; Schulder, Michael; Soriano Sanchez, Jose Antonio; Teo, Mario; Hernesniemi, Juha; Linzey, Joseph Raynor; Schwartz, Theodore H; Cohen-Gadol, Aaron A; et al.
Abstract: Even though neurosurgeons exercise these enormous and versatile skills, the COVID-19 pandemic has shaken the fabrics of the global neurosurgical family, jeopardizing human lives, and forcing the entire world to be locked down. We stand on the shoulders of the giants and will not forget their examples and their teachings. We will work to the best of our ability to honor their memory. Professor Harvey Cushing said: "When to take great risks; when to withdraw in the face of unexpected difficulties; whether to force an attempted enucleation of a pathologically favorable tumor to its completion with the prospect of an operative fatality, or to abandon the procedure short of completeness with the certainty that after months or years even greater risks may have to be faced at a subsequent session—all these require surgical judgment which is a matter of long experience." It is up to us, therefore, to keep on the noble path that we have decided to undertake, to accumulate the surgical experience that these icons have shown us, the fruit of sacrifice and obstinacy. Our tribute goes to them; we will always remember their excellent work and their brilliant careers that will continue to enlighten all of us.